Essays on Private Equity - Frederik Christian Vinten (Copenhagen Business School (CBS), 2008)
We study the impact of stock market valuations on delistings from European stock exchanges 1996-2004. Previous research has found that mergers and acquisitions (M&A) occur more often when market valuations are high. This is paradoxical since it implies that companies are more likely to engage in M&A when it is most expensive. In accordance with prior research we find that delistings by mergers and acquisitions are more likely when industry market-to-book values (q) are high. In contrast, we find no effect of industry q on going private transactions. The data also suggest that M&A are more likely to take place in bull years while going private transactions are relatively more likely in bear years. Our study is the first comprehensive study of delistings in Europe and the first study to demonstrate that going private transactions appear to be driven by different causal mechanisms than M&A.
hdl:10398/7682
Keywords: 650